Fluorescence sensing of mercury(ii) and melamine in aqueous solutions through microwave-assisted synthesis of egg-white-protected gold nanoclusters. Issue 14 (23rd March 2018) - Lin, Ying-Chiao; Wu, Tsunghsueh; Lin, Yang-Wei
Abstract : Microwave-assisted synthesis of fluorescent egg-white-protected gold nanoclusters for turn-off sensing of Hg(ii ) and turn-on sensing of melamine. Abstract : In this study, a microwave-assisted synthesis of fluorescent egg-white-protected gold nanoclusters (ew–AuNCs) for sensing Hg 2+ ions and melamine was developed, optimized, and evaluated. By conducting infrared spectrometry and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, we confirmed that clusters consisting of 22 Au atoms were successfully embedded in egg white. Transmission electron microscopy measurements revealed that the ew–AuNCs were well dispersed with an average diameter of 2.7 ± 0.7 nm. The ew–AuNCs exhibited red fluorescence emission ( λ em 648 nm) with high quantum yield (2.37%). In the presence of Hg 2+ ions, the fluorescence of these ew–AuNCs was quenched because of the Hg 2+ –Au + interaction. The relative change in fluorescence intensity at 648 nm was dependent on the concentration of Hg 2+ ions. Detection of melamine was based on the diminished fluorescence quenching of ew–AuNCs by Hg 2+ when melamine was added along with Hg 2+ . The limit of detection for Hg 2+ ions and melamine was 0.89 nM and 0.46 μM, respectively. Determination of Hg 2+ ions in a pond water sample and of melamine in milk and dog food samples was performed, and the recoveries from the developed method were >92.9%, confirming its potential for sensor applications.